(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Sumatra Island and its surroundings, Indonesia, are one of the most active tectonics in the world. The Aceh-Andaman earthquake, one of the most destructive earthquakes in the world, occurred there. It has attracted many earth scientists to apply various methods, including seismic tomography, to understand the island’s subsurface structure and tectonic system. This study is the first to delineate subsurface imaging beneath the island and its surroundings using a local-regional earthquake catalogue from the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) seismicnetwork. The tomographic imaging of P-wave (Vp) conducted in this study has successfully delineated subduction slabs (high Vp), partial melting zones (low Vp), volcanic arcs (low Vp), and Sumatran Fault zones (low Vp). The relationship between the subduction zone and the volcanic arc on the island can be seen on several vertical sections where a partial melting zone occurs at a depth of about 100 km, which functions as magma feeding for some volcanoes on the island. The oceanic slab model also exhibits a more pronounced and steeper slope towards the southern regions of Sumatra Island, possibly attributed to the slab’s aging process in that direction. The results highlight the importance of the BMKG seismic network in imaging local-regional subsurface structures beneath Indonesia’s archipelago, especially for the main islands such as Sumatra.